Exploring Challenges and Strategies for Improving the Quality of Education : Integrative Literature Review - Hidayat, Nur; Andriani, Fitri; Yoenanto, Nono Hery (Universitas Pendidikan Ganesha, 2024)
The issue of low-quality education on a global scale, particularly pronounced in Indonesia, presents multifaceted challenges spanning from elementary to tertiary education levels. This study endeavors to explore these challenges comprehensively and proffer strategies aimed at ameliorating education quality. By conducting an extensive literature review comprising 18 articles sourced from esteemed databases including Science Direct, Scopus, Web of Science, EBSCO, and Google Scholar, a range of innovative solutions has been delineated. These encompass modular training paradigms, effective management methodologies within madrasahs, implementation of transformational leadership approaches, methodologies for fostering student engagement, integration of technology, and facilitation of innovative educators. Despite the intricate nature of the challenges encountered within the Indonesian education system, discernible prospects for innovation and enhancement persist. Active engagement of stakeholders, notably teachers and school principals, emerges as pivotal for instigating sustainable changes. Furthermore, the identification of research lacunae, notably in the domain of early childhood education, underscores the imperative for a more expansive research agenda. This study stands to significantly enrich the understanding of education challenges and pioneering strategies, thus laying a robust groundwork for future advancements in education quality.